Comparison of the effectiveness of couple therapy based on object relationships and solution-oriented couple therapy on the emotional expression of spouses with marital conflict - Hosseini , Fatemeh; Vakili , Parivash; Abolmaali Alhosseini , Khadijeh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study was aimed to determine the effectiveness of couple therapy based on object relationships and compare it with solution-oriented couple therapy on the emotional expression of spouses with marital conflict. Method: The present study was quasi-experimental with pre-test and post-test with a two-month control and study groups and a statistical population of 192 couples referring to Hekmat and Saadat Counseling Centers in the first six months of 2019. After screening the subjects with King and Ammons (1990) Emotional Expression Questionnaire, 60 couples who got less than 40 scores from the cut-off point were selected by convenience sampling method and were randomly placed in the Object Relationship Couple Therapy study groups (10 couples), the solution-oriented couple therapy study group (10 couples) and control group (10 couples) . The first study group received eight 90-minute sessions of Donovan Object Relationship Couple Therapy Intervention (2013), and the second study group received the MacDonald Solution Axis Couple Therapy intervention for eight 90-minute sessions (2007), and the control group did not receive any intervention. The data were analyzed using repeated measures mixed variance analysis. Results: The findings showed the effect of object relationship couple therapy intervention on positive emotional expression (F = 114.76, P = 0.001), emotional intimacy expression (F = 228.85, P = 0.001) and negative emotional expression (F = 34.88, P = 0.001). And it showed the effect of solution-oriented couple therapy intervention on positive emotional expression (F = 49.96, P = 0.001), emotional intimacy expression (F = 116.30, P = 0.001), negative emotional expression (F = 16.46, P = 0.004) and the stability of this effect in the follow-up stage. Conclusion: The results of this study indicate that object relations couple therapy intervention and solution-oriented couple therapy are appropriate methods to increase positive emotional expression and emotional intimacy expression and reduce negative emotional expression in spouses with marital conflict.